Perilaku yang berhubungan dengan Menyusui Eksklusif pada Bayi Usia 6-12 Bulan di Kelurahan Banjaran Kota Kediri - Nining Tyas Triatmaja; Veny Astika Saraswati (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Infectious diseases in infants correlated with non-exclusive breastfeeding. Exclusive breastfeeding rates in Indonesia are still low. Breastfeeding behavior such as the implementation of early initiation of breastfeeding is thought to be related to exclusive breastfeeding. This study aimed to analyze the factors that associated with exclusive breastfeeding in infants aged 6-12 months old. The study design was cross-sectional using total sampling technique. Total samples was 41 mothers with children aged 6-12 months old in the Banjaran Village, Kediri City. Data were analyzed using the ChiSquare test. The results showed the prevalence of exclusive breastfeeding, the implementation of early initiation of breastfeeding, the feeding of prelacteal food, the feeding of early complementary food, namely 24.4%, 41.1%, 48%, and 36.5%. The implementation of early initiation of breastfeeding and prelacteal feeding was significantly related to exclusive breastfeeding. The support of health workers for the provision of education and mentoring for early initiation of breastfeeding needs to be increased as an effort to succeed in breastfeeding success.